Association of autoimmunity with survival in patients with recurrent/metastatic head and neck squamous cell carcinoma treated with nivolumab. (December 2020) - Economopoulou, Panagiota; Kotsantis, Ioannis; Papaxoinis, George; Gavrielatou, Niki; Anastasiou, Maria; Pantazopoulos, Anastasios; Kavourakis, George; Gkolfinopoulos, Stavros; Panayiotides, Ioannis; Delides, Alexandros; Psyrri, Amanda
Highlights: Immune-related adverse events (irAEs) occur due to T cell activation post immunotherapy. We sought to determine the correlation of irAEs with outcome in patients with HNSCC. We found that the occurrence of irAEs was an independent prognosticator for survival. IrAEs could be a useful biomarker for improved outcome in patients with HNSCC. Abstract: Objectives: Immune checkpoint inhibitors (ICIs) are associated with immune-related adverse events (irAEs) that occur as a consequence of enhanced immune response due to T-cell activation. The objective of this retrospective study was to investigate the association between irAEs and disease outcome in patients with recurrent/metastatic (R/M) head and neck squamous cell carcinoma (HNSCC). Materials and methods: This study included 89 patients with R/M HNSCC who were treated with nivolumab in our center from October 2015 to January 2020. Overall survival (OS) and post-progression survival (PPS) were calculated from the date of nivolumab initiation or from the date of progression on nivolumab respectively to the date of death or censored at the last date of follow up. Results: Twenty-four patients (27%) developed irAEs, with more common thyroiditis (N = 13, 14.6%). ORR did not differ between patients with irAEs (29.2%) and patients without irAEs (21.9%, p =  0.576). Median PFS was similar between the two groups (3.1 months for patients with irAEs vs. 2.6 months for patients without irAEs, p =  0.412). Median OS was significantly longer in patients with irAEs (17.9 vs. 6.3 months in patients without irAEs, log-rank p =  0.004). Additionally, median PPS was significantly improved in patients who developed irAEs (10.2 months vs. 2.8 months for patients without irAEs, log-rank p  = 0.001). In multivariate analysis, the development of irAEs and response to nivolumab were shown to be independent prognostic factors for favorable OS and PPS. Conclusions: The development of irAEs is a strong predictor of improved survival in patients with advanced HNSCC treated with nivolumab.